Associations between single nucleotide polymorphisms in the FAS pathway and acute kidney injury. Issue 1 (December 2015) - Bhatraju, Pavan; Hsu, Christine; Mukherjee, Paramita; Glavan, Bradford; Burt, Amber; Mikacenic, Carmen; Himmelfarb, Jonathan; Wurfel, Mark
Abstract Introduction To determine whether single nucleotide polymorphisms (SNPs) inFAS and related genes are associated with acute kidney injury (AKI) in patients with acute respiratory distress syndrome (ARDS). Methods We studied 401 (Caucasian N = 310 and African-American N = 91) patients aged ≥ 13 years with ALI who enrolled in the Fluid and Catheter Treatment Trial (FACTT) between 2000 and 2005 from 20 North American centers. We genotyped 367 SNPs in 45 genes of the Fas/Fas ligand pathway to identify associations between SNPs in Fas pathway genes and the development of AKI by day 2 after enrollment in FACTT, adapting Acute Kidney Injury Network (AKIN) criteria. Written informed consent was obtained from participants or legally authorized surrogates in the original FACTT study and available to use for secondary analysis. Results In Caucasian patients, we identified associations between two SNPs and the incidence of AKI (stage 1 and above): rs1050851 and rs2233417; both are found within the gene for nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (NFKBIA ). For rs1050851 and rs2233417, the odds ratios (ORs) were 2.34 (95 % confidence interval (CI) = 1.58–3.46, p = 1.06 × 10−5, FDR = 0.003) and 2.46 (CI = 1.61–3.76, p = 1.81 × 10−5, FDR = 0.003) for each minor allele, respectively. The associations were stronger still for AKIN stage 2–3 with respective ORs 4.00 (CI = 2.10–7.62, p = 1.05 × 10−5, FDR = 0.003) and 4.03 (CI = 2.09–7.77, p = 1.88 × 10−5, FDR = 0.003) for each minor allele homozygote. We observed no significant association between these SNPs and AKI in the smaller subset of African Americans. Conclusion In Caucasian patients with ALI, the presence of minor alleles in two SNPs inNFKBIA was strongly associated with the development of AKI. Trial registration NCT00281268 . Registered 20/01/2006.